Can Elastosonography Be Useful in Improving Diagnosis and Prognosis of Acute Muscle Injuries? - Cianforlini, Marco; Ulisse, Serena; Coppa, Valentino; Grassi, Marco; Rotini, Marco; Gigante, Antonio (Joints, 2018)
Purpose The objective of this study was to investigate the ability of elastosonography (USE) in the identification of different grades of muscular injuries, comparing its effectiveness with traditional ultrasound (US) survey and by relating the results to the clinical classification of muscular pain.Methods In the period between August 2014 and May 2016, we conducted a prospective cohort study on a population of 34 young male professional athletes belonging to the same under-17 football club (Ancona 1905). Injuries were recorded according to location, type, mechanism, recurrence, and whether they occurred with or without contact. Muscle pain was classified, after a physical examination, according to the classification of Mueller-Wohlfahrt et al. All athletes were evaluated by musculoskeletal US and USE in hours following the trauma/onset of pain.Results Seventy injuries were documented among 19 players. Muscle/tendon injuries were the most common type of injury (49%). USE showed areas of edema in nine lesions that were negative at the US examination and previously classified as fatigue-induced muscle disorders. These nine players took more time to return to physical activity compared with others with injuries classified into the same group, but negative at USE evaluation.Conclusion USE is a valuable aid in the diagnosis and prognostic evaluation of muscle injury, as it detects pathologic changes that are not visible with the B-mode US.Level of Evidence This is a Level III, observational cohort study.
Keywords: football; muscle injuries; muscle pain; ultrasound; elastosonography